The Influence Of K-Pop Group “Treasure” As Brand Ambassador of Ruang Guru on Consumer Purchase Decisions (Journal of Business and Management, 2022)
Business competition has gotten increasingly tough with a huge number of students in Indonesia, as well as the trend of online learning during the outbreak, there is surely a chance for education companies to develop their product market. Ruangguru, an educational startup company, chose TREASURE as the Ruangguru Learning Ambassador as part of the company's marketing strategy to reach a wider audience. Using mixed method approach to understand deeper the problems and came out with conclusion through statistical analysis, PLS-SEM method, found that the about half of the students are aware that TREASURE is the Brand Ambassador of Ruangguru. The purpose of this research is to assess whether Ruangguru made the right decision in selecting TREASURE as the Brand Ambassador, as well as whether TREASURE as the Ruangguru Brand Ambassador influences consumer purchasing decisions. The results revealed that Brand Ambassador and Brand Image variables both have significant influence on the consumer purchasing decisions, while the Brand Awareness has no significant influence. The result of this research hopefully can give benefits to readers, future researchers, and online educational platform management to develop their marketing strategies.Brand Ambassador, Brand Awareness, Brand Image, Purchase Decision, Education